Differences between calcifying epithelial odontogenic tumor and calcifying odontogenic cyst through panoramic radiograph: a scoping review - Regrina Setiawan; Ria Noerianingsih Firman; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: This review article is aimed to describe the radiographic features of CEOT and COC to determine the differences between the two lesions on panoramic radiographs. Review: This research is a descriptive study using scoping review method based on the Preferred Reporting Items for Systematic Review and Meta-analysis for Scoping Review (PRISMA-Scr). This study examines English and Indonesian articles of CEOT and COC with panoramic radiography as a diagnostic tool published in 2015 – 2021. Relevant articles were obtained from searches using keywords and inclusion criteria on PubMed, PMC NCBI, and hand searching techniques. A total of 32 articles were identified at initial study identification. Duplication, title and abstract, and full-text inspection consecutively excluded 1, 3, and 8 articles. A total of 20 eligible articles were included in this study, 10 cases of Calcifying Epithelial Odontogenic Tumor and 10 cases of Calcifying Odontogenic Cyst. Conclusion: The differences between COC and CEOT on panoramic radiographs are COC is more commonly found in the anterior region than CEOT and COC tends to occur in the periapical or lateral part of adjacent teeth and causes root resorption, whereas CEOT tends to be located at the crown of impacted teeth. There aren’t any pathognomonic radiographic findings from the CEOT and COC, so a definitive diagnosis still requires histopathological analysis.